Coauthorship in Regional Science: A Case Study of the WVU RRI Research Community. (July 2018) - Chen, Jing; Jackson, Randall
The year 2015 marked the fiftieth anniversary of West Virginia University's (WVU) Regional Research Institute (RRI), which has played an important role in many scientific collaboration networks. Through social network analysis (SNA) focusing on the RRI research community since its inception in 1965, this article illustrates the role that organizations and the networks they promote can play in scientific problem domains, promoting scholarly collaborations and coauthorship in the field of regional science. We analyzed an evolving WVU RRI coauthorship network that has grown and gained in complexity over time in terms of (1) global metrics, (2) components and cluster analysis, (3) centrality, and (4) PageRank and AuthorRank. The results of these analyses depict a well-developed and influential scientific collaboration structure within both WVU and the regional science research community.